Regional Difference in Myelination in Monocarboxylate Transporter 8 Deficiency: Case Reports and Literature Review of Cases in Japan - Iwayama, Hideyuki; Tanaka, Tatsushi; Aoyama, Kohei; Moroto, Masaharu; Adachi, Shinsuke; Fujisawa, Yasuko; Matsuura, Hiroki; Takano, Kyoko; Mizuno, Haruo; Okumura, Akihisa (Frontiers in Neurology, 2021)
Background: Monocarboxylate transporter 8 (MCT8) is a thyroid hormone transmembrane transporter protein. MCT8 deficiency induces severe X-linked psychomotor retardation. Previous reports have documented delayed myelination in the central white matter (WM) in these patients; however, the regional pattern of myelination has not been elucidated. Here, we describe the regional evaluation of myelination in four patients with MCT8 deficiency. We also reviewed the myelination status of previously reported Japanese patients with MCT8 deficiency based on magnetic resonance imaging (MRI). Case reports: Four patients were genetically diagnosed with MCT8 deficiency at the age of 4–9 months. In infancy, MRI signs of myelination were observed mainly in the cerebellar WM, posterior limb of internal capsule, and the optic radiation. There was progression of myelination with increase in age. Discussion: We identified 36 patients with MCT8 deficiency from 25 families reported from Japan. The available MRI images were obtained at the age of <2 years in 13 patients, between 2 and 4 years in 6 patients, between 4 and 6 years in 3 patients, and at ≥ 6 years in 8 patients. Cerebellar WM, posterior limb of internal capsule, and optic radiation showed MRI signs of myelination by the age of 2 years, followed by centrum semiovale and corpus callosum by the age of 4 years. Most regions except for deep anterior WM showed MRI signs of myelination at the age of 6 years. Conclusion: The sequential pattern of myelination in patients with MCT8 deficiency was largely similar to that in normal children; however, delayed myelination of the deep anterior WM was a remarkable finding. Further studies are required to characterize the imaging features of patients with MCT8 deficiency.